COMMUNITY SATISFACTION OVER THE BPJS PATIENT SERVICE IN CLINICS SHOULDER (studies in Clinics shoulder) - SIALLAGAN, YESSI SIALLAGAN; PANGKEY, MASJE SILIJA; PALAR, NOVIE febrina (Sam Ratulangi University, 2018)
This research is aimed to find out the satisfaction of public service of Social Insurance AdministrationOrganization (BPJS) patient in Puskesmas Bahu. On the basis of Law No. 25 of 2009 on Public ServiceStandards, the service standard has been determined that the service unit of the state is obliged to serve everycitizen and citizen to fulfill his basic rights and needs within the framework of public services. Including servicesprovided by the health services of the Puskesmas unit it is important that the satisfaction of the community canbe measured by the established standards, the satisfaction of service for BPJS patient service at PuskesmasBahu in terms of service, system, mechanism and procedure, Products Services, Facilities, infrastructure, andfacilities, Executing Competencies. Of the seven indicators of public service standards, there is the result thatit states less satisfied with facilities, infrastructure and facilities, service products, is satisfied with short servicetime, BPJS user fee or tariff is appropriate and satisfied with service requirements, system and servicemechanism, at the Bahu Puskesmas from interviews and field observations.Keywords: Public Satisfaction, Service